LEARNER CENTERED CURRICULUM IN THE EFL CLASSROOM IN INDONESIA - Weda Sukardi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2014)
Learner Centered Curriculum in the teaching of English in the classroom setting needs attention from educational practitioners, especially teachers of English. This is because; good curriculum hopefully will give beneficial contribution to the quality of teaching of English in Indonesia which is assumed today very low. This paper discusses a variety of issues deal with curriculum. Those issues are identification of curriculum problem, curriculum design, characteristics of ideal curriculum, curriculum development in Indonesia, and learner centered curriculum.